Gel pack reduced postoperative pain in benign gynecologic surgery: A randomized controlled trial - Wanlayanee Nuangpho; Sukanya Srinil; Thumwadee Tangsiriwatthana; Maleechat Sripipattanakul (The Royal Thai College of Obstetricians and Gynaecologists, 2018)
Objectives: To examine the effectiveness of gel pack for reducing postoperative pain in patient who undergoes exploratory laparotomy for benign gynecologic surgery.Materials and Methods: Twenty eight participants who underwent benign gynecological surgery under general anesthesia at Khon Kaen Hospital in March 2016 were randomized by computer generated into two groups: gel pack group (N=14) and control group (N=14). Gel pack was applied at 2 hours after operation for 20 minutes and pain score was measured using visual analog scale (VAS) at 2 (baseline), 6 and 24 hours, respectively. The VAS was divided into two grades by pain-intensity; mild (VAS < 4), and moderate to severe (VAS ≥ 4). The comparison of pain-intensity was analyzed by Fisher exact test (p < 0.05).Results: Gel pack was statistically significant reduced postoperative pain from moderate-severe pain to mild pain intensity at 6 hours compared with control group (11 to 8 cases versus 14 to 14 case, p = 0.01, 95%CI 0.03-0.89). There was no statistically significant difference in opioid consumption, hospital stay and wound infection between two groups. Conclusion: Gel pack can reduce postoperative pain at 6 hour in benign gynecological operation without complication.